2013
DOI: 10.1186/1471-2458-13-809
|View full text |Cite
|
Sign up to set email alerts
|

Female genital mutilation among Iraqi Kurdish women: a cross-sectional study from Erbil city

Abstract: BackgroundIraqi Kurdistan region is one of the areas where female genital mutilation is reportedly widely practiced but inadequately studied. The aim of this study was to determine (i) the prevalence of female genital mutilation among Muslim Kurdish women in Erbil city, (ii) the patterns and types of female genital mutilation, (iii) the factors associated with this practice and (iv) women’s knowledge and attitudes towards this practice.MethodsA cross-sectional study was conducted in the primary health care cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
97
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(110 citation statements)
references
References 11 publications
5
97
4
Order By: Relevance
“…Even though no religious scripts state FGC as religious requirement, some people relate FGC to Islamic religion [14]. On the contrary, the current data reports that, FGC was not religious requirement.…”
Section: Discussioncontrasting
confidence: 72%
“…Even though no religious scripts state FGC as religious requirement, some people relate FGC to Islamic religion [14]. On the contrary, the current data reports that, FGC was not religious requirement.…”
Section: Discussioncontrasting
confidence: 72%
“…Saleem et al found that children of uneducated mothers were eight times more likely to have FGM/C compared with children of mothers with over nine years of education . Both the education of the girl's father and the employment status of the girl's mother have been shown to be significant factors associated with FGM/C . FGM/C is usually performed in childhood, and may bear little relationship with current socio‐demographic status.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation was that the subject of FGM/C is very sensitive. It is known that the self reporting of different forms of FGM is unreliable and underreporting is common but also overreporting has been documented . While the FGM/C‐status was not examined, only asked about, underreporting is more likely as is recall bias, as not all those interviewed would be able or willing to tell about their FGM/C situation in the interview.…”
Section: Discussionmentioning
confidence: 99%
“…EDHS (2015) (El Zanaty F,2015) reported similar findings, as more than half of women thought that FGC is a religious requirement and less than half of them believed that the practice deters adultery. Furthermore, Yasin B et al (2013) reported that the common reasons for practicing FGC were cultural tradition and religion.…”
Section: Discussionmentioning
confidence: 99%